2019
DOI: 10.15637/jlecon.6.027
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Logistical and Supply Chain on the Performance of Shallot Farmers East Java

Abstract: This study aims to analyze and explain logistical activities in the shallot supply chain in East Java Province. Data were collected using a questionnaire from 200 shallot farmers as instruments in the study sample. Data analysis using SEM PLS method with SmartPLS 3.0 software. The results of this study indicate that transportation has a significant influence on integrative supply chains and business performance. This means that the higher the role of partners to producers to prepare transportation in the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…These criteria include vulnerability, treadmilling, leaps forward, and state institutional capacity [18]. The previous study revealed that transportation significantly influences the integrative supply chain and shallot products' business performance [19].…”
Section: Introductionmentioning
confidence: 99%
“…These criteria include vulnerability, treadmilling, leaps forward, and state institutional capacity [18]. The previous study revealed that transportation significantly influences the integrative supply chain and shallot products' business performance [19].…”
Section: Introductionmentioning
confidence: 99%